Do elite soccer players cover longer distance when losing? Differences between attackers and defenders - Lago-Peñas, C.; Kalén, A.; Lorenzo-Martinez, M.; López-Del Campo, R.; Resta, R.; Rey, E. (International Journal of Sports Science & Coaching, 2021)
This study aimed to evaluate the effects playing position, match location (home or away), quality of opposition (strong or weak), effective playing time (total time minus stoppages), and score-line on physical match performance in professional soccer players using a large-scale analysis. A total of 10,739 individual match observations of outfield players competing in the Spanish La Liga during the 2018-2019 season were recorded using a computerized tracking system (TRACAB, Chyronhego, New York, USA). The players were classified into five positions (central defenders, players = 94; external defenders, players = 82; central midfielders, players = 101; external midfielders, players = 72; and forwards, players = 67) and the following match running performance categories were considered: total distance covered, low-speed running (LSR) distance (0-14 km · h-1), medium-speed running (MSR) distance (14-21 km · h-1), high-speed running (HSR) distance (>21 km · h-1), very HSR (VHSR) distance (21-24 km · h-1), sprint distance (>24 km · h-1) Overall, match running performance was highly dependent on situational variables, especially the score-line condition (winning, drawing, losing). Moreover, the score-line affected players running performance differently depending on their playing position. Losing status increased the total distance and the distance covered at MSR, HSR, VHSR and Sprint by defenders, while attacking players showed the opposite trend. These findings may help coaches and managers to better understand the effects of situational variables on physical performance in La Liga and could be used to develop a model for predicting the physical activity profile in competition.